A Proposed Business Strategy To Improve Competitive Advantage In Healthyle Startups - Rabbani, Pandu Syauqi; Aziz, Fauzan; Arief, Mochammad Muminto (Entrepreneurship Faculty, Universitas Garut, 2024)
Healthyle aims to alleviate consumer concerns about catfish quality through a rigorous certification process. The city of Bogor and its surroundings were selected as the target market due to the high demand for catfish in the area. The ultimate goal of this assignment is to aid Healthyle in devising an effective business strategy, positioning it to potentially become a significant player in the catfish farming industry in Indonesia, particularly in and around Bogor. The strategic analysis of a company involves assessing its internal and external environment. This includes evaluating internal factors such as strengths and weaknesses using the Internal Factor Analysis Summary (IFAS) and Value Chain analysis. External factors, including opportunities and threats, are assessed using the External Factor Analysis Summary (EFAS), PESTEL analysis, and Porter’s Five Forces model. The Competitive Profile Matrix (CPM) compares the company’s performance with its competitors, while the Strategic Factor Analysis Summary (SFAS) integrates findings from IFAS and EFAS. This approach is expected to be profitable short-term and build a sustainable reputation long-term. The research offers insights into the industry’s competitive dynamics and strategy formulation.